2020
DOI: 10.1093/ajcn/nqaa192
|View full text |Cite
|
Sign up to set email alerts
|

Two weeks of early time-restricted feeding (eTRF) improves skeletal muscle insulin and anabolic sensitivity in healthy men

Abstract: Background Altering the temporal distribution of energy intake (EI) and introducing periods of intermittent fasting (IF) exert important metabolic effects. Restricting EI to earlier in the day [early time-restricted feeding (eTRF)] is a novel type of IF. Objectives We assessed the chronic effects of eTRF compared with an energy-matched control on whole-body and skeletal muscle insulin and anabolic sensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 48 publications
3
129
6
Order By: Relevance
“…In addition, one recent study has even reported that diet-induced reductions in fat-free mass can be offset by only slightly increasing the daily fasting period from 18 to 20 hours (27). It therefore appears that losses of fat-free mass are possible even with less protracted periods of limited nutrient delivery than implemented in the present study, and so, further research is needed to examine the potential for a more sustained catabolic state to result in atrophy of lean soft tissue mass or to improve anabolic sensitivity (16).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, one recent study has even reported that diet-induced reductions in fat-free mass can be offset by only slightly increasing the daily fasting period from 18 to 20 hours (27). It therefore appears that losses of fat-free mass are possible even with less protracted periods of limited nutrient delivery than implemented in the present study, and so, further research is needed to examine the potential for a more sustained catabolic state to result in atrophy of lean soft tissue mass or to improve anabolic sensitivity (16).…”
Section: Discussionmentioning
confidence: 63%
“…For example, early time-restricted feeding (fasting from 1500 h daily) in men with prediabetes improved their insulin sensitivity within 5 weeks without losing weight, simply by extending their usual overnight fast to 18 hours (15). This effect on insulin sensitivity has since been confirmed in healthy young adults after only 2 weeks of fasting for 16 hours from 1600 h each day (16) and after 8 weeks of simply restricting typical daily meals to an 11-hour period ending at 1900 h (17). The other common form of intermittent fasting that routinely involves such protracted postabsorptive periods is complete alternate-day fasting (no energy intake whatsoever during fasting days), yet almost no research has examined fasting periods that span an entire day.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, TRF had no effect on body weight over the 8-week period; however, hindlimb muscle mass was smaller in both fasting groups. Some groups have shown a maintenance of muscle mass during TRF, but most of these studies combine the fasting with resistance exercise [ 21 , 22 , 23 , 24 ], whereas we utilized endurance exercise which may have a less potent anabolic effect on the muscle. Interestingly, it has been shown that TRF decreased IGF-1 and testosterone levels [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TRF induced between 0800 and 1400 improved the 24-h glucose levels and increased the expression of the anti-aging gene SIRT1 and the autophagy gene LC3A in the blood compared with the TRF induced between 0800 and 2000 (Jamshed et al, 2019). In terms of skeletal muscle function, 2 weeks of TRF induced between 0800 and 1600 improves insulin and anabolic responses in the skeletal muscle of healthy young men (Jones et al, 2020). Indeed, TRF increased the skeletal muscle uptake of glucose and branchedchain amino acids (BCAAs) (Jones et al, 2020).…”
Section: Therapeutic Potential Of Chrono-nutrition Against Are-related Muscle Dysfunctionsmentioning
confidence: 93%
“…In terms of skeletal muscle function, 2 weeks of TRF induced between 0800 and 1600 improves insulin and anabolic responses in the skeletal muscle of healthy young men (Jones et al, 2020). Indeed, TRF increased the skeletal muscle uptake of glucose and branchedchain amino acids (BCAAs) (Jones et al, 2020). The effects of TRF in men who are overweight/obese have been elucidated using the circadian transcriptome of skeletal muscle (Lundell et al, 2020).…”
Section: Therapeutic Potential Of Chrono-nutrition Against Are-related Muscle Dysfunctionsmentioning
confidence: 99%